Education in equality: Training program for the transversalization of the gender approach: Una propuesta transdisciplinar para su materialización efectiva - Marcelo Gómez, Giovanna Fiorella; Alegre Jara, Maribel Enaida (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The “Education in Equality” program comes from a descriptive projective study, designed to improve the appreciation of the gender approach in teachers of an educational institution, based on scientific theories, the characteristics of the unit of analysis -whose sample was 30- and the level of appreciation of the gender approach identified with a questionnaire with a reliability of 0.963 in the Cronbach’s Alpha. This article seeks to present it as a training program for the effective transversalization of the gender approach, developed and implemented under a holistic and transdisciplinary approach, through 15 educational workshops.